Pengurangan Kadar Racun Pada Pembuangan Pestisida Rusak - Rofienda Rofienda; sri pudji Rahayu (Balai Besar Kimia dan Kemasan, 1996)
Unused pesticide either damage pesticide from long term storage or unppropiate storage, it will be a big problem especially when it be disposed, because it will destroy the environment. For that reason, research on detoxification of damage pesticides with active ingredient monocrotophos, chlorpyriphos and profenophos using 10 % and 25 % concentration of sodium hidroxide (NaOH) and 10, 20 and 30 % concentration of lime were conducted.The result of the experiment showed that NaOH with 25 % concentration can decrease the concentration of monocrotophos, chlorpyripos and proferophos 77,5 %, 53,3 % and 91,8 % respectively. While 30 % concentration of lime decreased the concentration of monocrotophos, chlorpyripos and profenopos as 84,2 %; 46 % and 80,8 % respectively. Using of 25 % NaOH gave a better result compared then using 30 % of lime. However, from the economical point of view, lime was better.